Pengaruh Sistem Pembiayaan BUMDES Syari’ah Terhadap Peningkatan Perekonomian Masyarakat (Studi Pada Desa Wargaluyu Kecamatan Tanjungmedar) - Hamid, Abdul; Purwanti, Neli; Mulyana, Iwan; Syaripudin, Enceng Iip; Maulin, Mery (Jurnal Hukum Ekonomi Syariah, 2023)
This study aims to determine the effect of the Sharia BUMDES financing system on improving the community's economy.  This study was conducted using a quantitative approach. The number of samples used in this study was 58 respondents taken from participants from BUMDES Mekar Rahayu financing, Wargaluyu Village, Tanjungmedar District. The data sources obtained in this study are primary and secondary data sources. The results of this study show that the variable of the Sharia BUMDES financing system affects the economic improvement of the community. Based on the T test that has been carried out, it shows that the variables of the BUMDes sharia financing system have an influence on the variables of improving the community's economy.  Meanwhile, based on the R square test that has been carried out, it shows that the variable of the Sharia BUMDES financing system has an influence of 44.6%.  towards improving the economy of the community. While 55.4% are other factors that are not used as research indicators but are considered to have an influence on variable Y. Keywords: Financing, Sharia BUMDES, Community Economy;